Post-Traumatic Stress Disorder and Employment in Women Reporting Abuse: 5-Year Data from a Longitudinal Study - Gilroy, Heidi (Journal of family violence, 2021)
Intimate partner violence (IPV) is a common public health problem that has serious consequences for women in terms of health and functioning. Post-traumatic stress disorder (PTSD) is one of the major health issues that women face after experiencing intimate partner violence. There is evidence that sufficient and sustainable employment might decrease risk for PTSD in women who have experienced violence. The purpose of this study is to investigate if variables related to employment (i.e., income, hours worked per week, job benefits) affect risk for PTSD over 5 years after women left abusive relationships. Data collection took place between 2010 and 2016. To test the hypothesis that present employment variables predict the woman’s PTSD in the future, a series of conditional latent growth curve (LGC) models were conducted. The overall models indicated that there appears to be a consistent impact of economic factors on PTSD symptoms; however, the variable with the greatest impact was the number of hours worked. Women who had full-time or near full-time employment were at less risk to have PTSD in the future. These findings support efforts to increase access to full time work for women who have experienced intimate violence.